An expeditious synthesis of 6-Amido-(1H,3H)-Pyrimidine- 2,4-Diones from Uracil-6-Carboxylic Acid - Khan, Md Wahab; Haque, Md Enamul; Ahmed, Md Faiaz (Dhaka University Journal of Pharmaceutical Sciences, 2015)
2,4-Dichloro pyrimidine-6-carbonylchloride (2) was synthesized by refluxing uracil-6-carboxylic acid (orotic acid) with phosphorus oxychloride and phosphorus pentachloride. Compound (2) underwent a smooth coupling reaction with a number of substituted arylamines to yield 2, 4-dichloro-6-amidopyrimidines (8-12) which were converted to the corresponding 2, 4-dimethoxy-6-amidopyrimidines (13-17) on treatment with sodium methoxide in methanol. Compounds 13-17 afforded 6-amido-(1H, 3H)-pyrimidine-2, 4-diones (18-22) in good yield on refluxing with 6 M hydrochloric acid. These pyrimidinone derivatives may exhibit antiviral actitities. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21856 Dhaka Univ. J. Pharm. Sci. 13(1): 23-29, 2014 (June)